Introduktion: DANSKHEDENS ATTRAKTION - Redaktionen, TA (Tidsskriftet Antropologi, 2000)
Redaktionen: Lars Holmberg, Christian Kordt Højbjerg, Finn Kjær Jensen, Nina Johnsen, Katja Kvaale, Kennet Pedersen, Andreas Roestorff, Kirsten Rønne, Kirsten Marie Raahauge, Tine Tjørnhøj-Thomsen, Gertrud Øllgaard (ansv.).